Cerebellar signals drive motor adjustments and visual perceptual changes during forward and backward adaptation of reactive saccades. (4th January 2022) - Cheviet, Alexis; Masselink, Jana; Koun, Eric; Salemme, Roméo; Lappe, Markus; Froment-Tilikete, Caroline; Pélisson, Denis
Abstract: Saccadic adaptation (SA ) is a cerebellar-dependent learning of motor commands (MC ), which aims at preserving saccade accuracy. Since SA alters visual localization during fixation and even more so across saccades, it could also involve changes of target and/or saccade visuospatial representations, the latter (CDv ) resulting from a motor-to-visual transformation (forward dynamics model) of the corollary discharge of the MC . In the present study, we investigated if, in addition to its established role in adaptive adjustment of MC, the cerebellum could contribute to the adaptation-associated perceptual changes. Transfer of backward and forward adaptation to spatial perceptual performance (during ocular fixation and trans-saccadically) was assessed in eight cerebellar patients and eight healthy volunteers. In healthy participants, both types of SA altered MC as well as internal representations of the saccade target and of the saccadic eye displacement. In patients, adaptation-related adjustments of MC and adaptation transfer to localization were strongly reduced relative to healthy participants, unraveling abnormal adaptation-related changes of target and CDv . Importantly, the estimated changes of CDv were totally abolished following forward session but mainly preserved in backward session, suggesting that an internal model ensuring trans-saccadic localization could be located in the adaptation-related cerebellar networks or in downstream networks, respectively.